(untitled) (Research, Society and Development, 2022)
Objective: This study aimed to identify the interventions used by occupational therapists in palliative care of cancer patients at the end of life. Method: This is an integrative literature review study conducted in May 2020 in the databases and digital library PubMed, SCOPUS, LILACS, APA PsycNet, BDENF, SciELO, CINAHL and Web of Science. We found 3405 articles, of which original studies were included and in the English, Spanish or Portuguese languages, totaling 20 studies, organized in the Atlas.ti program and analyzed based on content analysis. Results: results indicate that the interventions are focused on evaluations, adaptations, symptom management, occupational roles, social participation, activities of daily living, instrumental and leisure activities, as well as active listening. Conclusion: The review made it possible to identify the interventions addressed in the care of cancer patients in palliative care by occupational therapists, pointing out how end-of-life care practices are conducted.